Assessment of Risk of Fall among Elderly (Indian Journal of Public Health Research & Development, 2020)
Assessment of risk of fall among elderly in selected community area, Kanchipuram district, Tamilnadu,India. The objectives are to assess the risk of fall among elderly in selected community area, To associatethe risk of fall with demographic variables in selected community area. The resrarch approach used for thestudy was Quantitative Approach Purposive sampling technique was used to select 60 samples. The datawere collected by using Fall Risk Assessment scale. The collected data were tabulated and analyzed. Thelevel of significance selected was p
Keywords: Assessment, Risk of fall, elderlypeople, level of risk.